Prevalence of Metallo-β-Lactamases in Acinetobacter Baumannii in Iran: A Review and Meta-Analysis - Mohammadpour, Bashir; Rouhi, Samaneh; Moradi, Masoud; Ramazanzadeh, Rashid; Saniyi, Ebrahim; Zandi, Sairan; Salimizand, Himen (Infectious Disorders - Drug Targets, 2019)
Acinetobacter baumannii (A. baumannii) is an important opportunistic pathogen that causes major public health concerns, especially in hospitalized patients due to acquisition of resistant genes. The aim of this study was to systematically review the published data on the prevalence and dispersion of metallo-β-lactamases (MBLs) genes in A. baumannii in different provinces of Iran and provide an overall prevalence rate using meta-analysis. All available national and international databanks from 2011 to 2017 were searched to find published studies. Quality of studies was assessed by STROBE. Due to the fact that a significant heterogeneity was observed, the random effects model was used to combine the results. Statistical analysis was performed by comprehensive meta-analysis (CMA) V2 software. Out of 78 articles, 28 were extracted based on certain inclusion and exclusion criteria. Most of the A. baumannii isolates were obtained from intensive care unit (ICU) ward of hospitals. Based on phenotypic and molecular detection tests, pooled prevalence of all MBLs was 58%, and blaVIM, blaIMP, and blaSPM-1 genes were estimated to be at 10.5, 6, and 5%, respectively. Based on the results, further attention should be given to report MBL genes in A. baumannii based on molecular detection rather than the phenotypic one. Furthermore, more effort should be focused on ICU sections in order to avoid the distribution of resistant genes.
Keywords: Acinetobacter baumannii